Relacje inwestorskie jako narzędzie budowania zaufania uczestników rynku kapitałowego - Krug, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The practical aim of this article is to determine the effectiveness of the investor relations used as a tool in building and strengthening the trust among the investment community. It is left without doubt, during the constant progress of economy investor relations are growing to become a significant issue in building trust among the investors. The article intends to clarify the basic problems of IR and its focus shifts from the question, "Shall we do it?" to the one of, "How to do it?". (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 265-278